DEVELOPMENT OF THE STUDENT'S PERSONALITY, PREPARATION OF STUDENTS FOR LIFE IN CONDITIONS OF INFORMATION PROGRESS - Sadiqova Kamilia Abidovna; Mirzarasulev Oybek Mirza-Anvarovich (Galaxy International Interdisciplinary Research Journal, 2023)
The current state of an educational institution is characterized by an increase in crisis phenomena in it, which is associated, on the one hand, with a massive delay in the physical and mental development of children, and on the other, with an ever-increasing gap between the potential level of learning material by students and the pedagogical technologies used in school. According to the survey, in schools only a small part of secondary school teachers work at a professional and creative level, using modern pedagogical technologies. The ongoing educational reforms of the Republic of Uzbekistan require modern pedagogical science to update knowledge and technologies as tools for improving the quality of the educational process in modern educational institutions. Numerous studies have proven that the quality of education largely depends on the chosen pedagogical technology and teaching method, as well as the presentation of new content to schoolchildren. It is possible to achieve good results in teaching the subject of biology through modern pedagogical technologies [5].